Code-switching practices of secondary school english and science teachers in the classroom - Then, Chen On (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study examined code-switching practices of secondary school English and Science teachers in the classroom. The participants were nine English teachers and nine Science teachers teaching Form One and Form Two classes for three secondary schools in Kuching. The theoretical framework for the analysis of code-switching functions is taken from Gumperz's (1982) semantic model. The data were collected by means of semistructured intetviews and classroom obsetvations of naturally occurring teacher discourse. Semi-structured intetviews were conducted to identify teachers' views on their reasons for code-switching The results from the analysis of the teachers' classroom codeswitching using showed that the teachers frequently code-switched for reiteration and quotation in English and Science classrooms. The results also showed that the teachers quoted students' answers to negotiate understanding of terms and concepts in classrooms. The teachers' reiteration of message enhanced the clarity of lessons. The teachers' codeswitching promoted meaningful communication and successful transfer of knowledge to students. The English teachers also used more addressee specification, personalisation and objectivisation to establish a more interpersonal communication with students as compared to Science teachers who tended to code-switch for quotations. Teachers also used a combination of code-switching functions to emphasise message, empower teacher and incorporate students' speech and text materials into teacher talk. The intetview results indicated that the teachers viewed code-switching as linguistic resource to help students to understand terms, instructions and concepts but they reported resetvations to code-switch due to language policies and concerns about students' learning. The findings 11 showed that the teacher reports on code-switching often do not match with codeswitching practices In actual classrooms suggesting code-switching occurs subconsciously.